2020
DOI: 10.26529/cepsj.742
|View full text |Cite
|
Sign up to set email alerts
|

Fraction Sense: An Analysis of Preservice Mathematics Teachers’ Cognitive Obstacles

Abstract: Research on cognitive obstacles related to fraction sense in preservice mathematics teachers is significant, because their success depends on their skills. The acquisition of fraction sense is a complicated problem requiring a strategy to solve it. This study presents cognitive obstacles with fraction sense tests in preservice who will teach in secondary schools. It focuses on the following categories of cognitive obstacles: epistemological (language representation, tendency to generalise and rely on intuition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In this research, an instrument to measure cognitive obstacles to negative fractions learning material has been developed. At the same time, previous studies revealed only a cognitive obstacle to positive fractions learning material [9], [26], [16]. Other researches showed the cognitive obstacle to negative integers [1], [27].…”
Section: Construct Validitymentioning
confidence: 93%
See 2 more Smart Citations
“…In this research, an instrument to measure cognitive obstacles to negative fractions learning material has been developed. At the same time, previous studies revealed only a cognitive obstacle to positive fractions learning material [9], [26], [16]. Other researches showed the cognitive obstacle to negative integers [1], [27].…”
Section: Construct Validitymentioning
confidence: 93%
“…The pre-service teachers in question had already finished the course of Mathematical Foundation and School Mathematics Development Studies 1. Both classes instill an understanding of numbers so that the candidates have sufficient cognitive knowledge to solve fraction problems [16]. The candidates were selected based on various abilities they already have.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous studies have revealed didactic obstacles in online learning based on teacher and student perceptions. There has not been much research on didactic obstacles to prospective teachers (Akkaya et al, 2021;Murniasih et al, 2020). This study aims to describe the didactic obstacles in terms of prospective teachers' perceptions regarding online learning.…”
Section: Introductionmentioning
confidence: 97%
“…Implementing online learning causes didactic obstacles in learning (Van & Thi, 2021). Didactic obstacles are part of cognitive obstacles (Brousseau, 1997;Murniasih et al, 2020). Didactic obstacles are caused by school teacher teaching (Nurjanah & Juliana, 2020;Mustika et al, 2018).…”
Section: Introductionmentioning
confidence: 99%